Kajian Yuridis Mengenai Legalitas Cryptocurrency di Indonesia - Ida Ayu Samhita Chanda Thistanti; I Nyoman Gede Sugiartha; I Wayan Arthanaya (Warmadewa Press, 2022)
Technological advances in the world are very helpful in payment systems that are safe, fast and confidential. Currently, it has also given birth to a rapidly growing currency, namely cryptocurrency, but Indonesia still does not have definite regulations regarding the use of cryptocurrencies. The purposes of this research are to examine the regulation of cryptocurrency legality based on the Indonesian Positive Law and to examine the legal sanctions in the event of a criminal use of cryptocurrency in Indonesia. The method used is normative legal research with a statutory approach. The legal materials used are primary and secondary legal materials that have authoritative properties. To obtain valid data in the field, the researcher uses library techniques, recording techniques, and combines it with normative legal research and makes a law that is both inductive and deductive. The data were analyzed by legal argumentation and descriptive analysis to obtain a systematic comprehensive picture. The results of the study reveal that the regulation of the legality of using cryptocurrencies in Indonesia is no longer referred to as â€œdigital moneyâ€, but â€œcommoditiesâ€ regulated by the Commodity Futures Trading Regulatory Agency in CoFTRA rules No. 3 of 2019 and CoFTRA No. 5 of 2019. It is expected that policy holders will issue strict regulations and sanctions related to the use of crypto currency for crimes against the use of cryptocurrencies for the public and investors as users of Crypto Assets in Indonesia.